2016
DOI: 10.1371/journal.pone.0150863
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evidence for the Efficacy of Ischemic Postconditioning against Renal Ischemia-Reperfusion Injury, a Systematic Review and Meta-Analysis

Abstract: BackgroundRenal ischemia-reperfusion injury (IRI) is a major cause of kidney damage after e.g. renal surgery and transplantation. Ischemic postconditioning (IPoC) is a promising treatment strategy for renal IRI, but early clinical trials have not yet replicated the promising results found in animal studies.MethodWe present a systematic review, quality assessment and meta-analysis of the preclinical evidence for renal IPoC, and identify factors which modify its efficacy.ResultsWe identified 39 publications stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In renal ischemia-reperfusion, ischemic preconditioning [ 14 ] and postconditioning [ 15 ] have both been successfully tested in laboratory environments. While remote renal ischemic pre- and postconditioning have also been investigated in a clinical setting, no consistent effect has been reported [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In renal ischemia-reperfusion, ischemic preconditioning [ 14 ] and postconditioning [ 15 ] have both been successfully tested in laboratory environments. While remote renal ischemic pre- and postconditioning have also been investigated in a clinical setting, no consistent effect has been reported [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 13 Although not as extensively evaluated, there is also reason for concern regarding the selective publication of preclinical animal studies. [14][15][16] As in clinical research, systematic review and meta-analysis has been instrumental in making publication bias in animal research transparent. Between 46% and 62% of preclinical systematic reviews find evidence of publication bias.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes, the best characterized type of EVs; are secreted nanovesicles (30–150nm in diameter) that contain proteins, lipids, mRNA and miRNAs [ 12 ]. Secreted exosomes interconnect cells, and convey the metabolic state of the originating cells, including protective responses to hypoxia [ 13 15 ]. For example, we have showed that renal exosomes released from hypoxia pre-conditioned renal tubular cells (i.e., HPC exosomes) prevented most manifestations of severe AKI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%